Línea de calibración para relevamientos geofísicos aéreos por espectrometría de rayos gamma, área Lago Musters, provincia del Chubut - López, Luis E. (1998)
A local calibration test strip to determine both the system sensitivities and height attenuation coefficients was defined at the Musters Lake area, for its use in airborne spectrometric surveys in the south Patagonian region. The selected calibration range presents both low and uniform radioelement concentrations. The mean spectrometric values obtained at ground level were 1.8 % K, 1.6 ppm eU and 7.3 ppm eTh while the variation coefficients were 7.5 %, 27.0 %, and 10.2 %, respectively.